Роль ЄС у поглибленні економічної співпраці країн Агадирської угоди та Магрибу в умовах посткризового відновлення - Резнікова, Н.В.; Відякіна, М.М. (Культура народов Причерноморья, 2013)
Досліджено специфіку економічного співробітництва країн Союзу арабського Магрибу,
Агадирської угоди та ЄС. Виокремлено чинники, що перешкоджають поглибленню інтеграції країн
регіону. До внутрішніх причин їх інституційної та економічної вразливості віднесено однотипність
економік, подібність профілю спеціалізації, відсутність організаційних, фінансово-економічних
структур тощо. Аргументується, що для зміцнення колективних договорів і встановлення політичної
стабільності в регіоні, ЄС варто докласти зусиль до поглиблення регіональної інтеграції.
Ключові слова: Магриб, Агадирська угода, експортний потенціал, двосторонні угоди, ПІІ. Исследуется специфика экономического сотрудничества стран Союза арабского Магриба,
Агадирского соглашения и ЕС. Выделены факторы, препятствующие углублению интеграции стран
региона. К внутренним причинам уязвимости последних отнесены однотипность экономик, схожесть
профиля специализации, отсутствие организационных, финансово-экономических структур и т.п.
Аргументируется, что для укрепления коллективных соглашений и достижения политической
стабильности в регионе, усилия ЕС необходимо сосредоточить на углублении региональной интеграции.
Ключевые слова: Магриб, Агадирское соглашение, экспортный потенциал, двусторонние соглашения,
ПИИ. The article reveals the specifics of regional economic cooperation between the states of the Agadir
Agreement, Arab Maghreb Union and the European Union in times of post-crisis recovery and political
instability in the region. The authors argue that despite the attention given to the investment agreements, the EU
policy should provide more support to the economic development of the southern partners.
The authors define the factors hindering the strengthening of the integration in the region, namely production of
a narrow set of products along with the absence of division of labor; low income and lack of solvent demand,
which shifts the focus to the markets in developed countries as consumers of raw natural resources; the need of
industry protection limiting the scope and potential for the regional integration; highly differentiated level of
economic development within the region. The internal causes of institutional and economic vulnerability of the
group under analysis include similarity of the economies, industrial and agricultural specialization; lack of
organizational, financial and economic structures; lack of necessary experience and elaborated partnerships,
finances; poor political will to develop the mechanism of practical implementation of decisions. It is argued that
the EU should foster regional integration, which will strengthen the collective agreements and promote political
stability in the region.
Keywords: Maghreb, Agadir Agreement, export potential, bilateral agreements, FDI.